PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA - Muslikhah, Imroatul; Nuruddin, Muhammad (PGMI UNHASY, 2025)
The CPS model emphasizes creative problem solving by involving stages such as problem exploration, idea generation, solution selection, and implementation. The research method used is an experimental design with a pretest-posttest control group design. The study population consist of V classs SDN Kayangan 1 Diwek, with 17 students. The research instrument is a learning motivation questionnaire adapted from the theory of learning motivation. Data were analyzed using paired sample t test and independent sample t-test to observe differences in learning motivation before and after the implementation of the CPS model. The results show a calculated t-value of -3.038, while the t-table values is -2.119, with a significance value (2-tailed) of 0.008, which is smaller than 0.05. this means that the calculated t-values is greater than the t-table values, leading to the acceptance of the alternative hypothesis (H1) and rejection of the null hypothesus (H0). Thus, it can be concluded that the is a significant increase in students learning motivation after implementing the CPS model compared to the control group using conventional models. Factors such as active students engagement, creative thinking, and systematic problem solving contribute to the increased learning motivation.. therefore, the CPS learning model can serve as an effective alternative to enhance students’ learning motivation in Pancasila Education.